PENGARUH KOMPETENSI DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI INTRINSIK SEBAGAI VARIABEL INTERVENING - Umi Hanik Ampreliana; Kusuma Chandra Kirana; Didik Subiyanto (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
The apurpose aof athis astudy awas ato adetermine athe aeffect aof acompetence aand aleadership aon aperformance awith aintrinsic amotivation aas aan aintervening avariable. aThis astudy aused aquantitative amethods awith athe aform aof amultiple alinear aanalysis aand arespondents aIn athe astudy, a88 arespondents awho awere aemployees aof athe aDepartment aof aTransportation aof aKediri aRegency awere aalso athe asample. aData awere acollected aby adistributing aquestionnaires. aThe adata aquality atest aincludes avalidity aand areliability atests.the analysis used in statistical test, classical assumption test, multiple regression analysis and sobel test. The aresults aof athe astudy aindicate athat: Competnce has a significant effect on intrinsic motivation; leadership has an effect on intrinsic motivation; competence has an effect on performance; leadership influences performance; intrinsic motivation is not able ito intervening competence on performance; intrinsic motivation is not capable of intervening leadership on performance